2022
DOI: 10.32714/ricl.10.01.06
|View full text |Cite
|
Sign up to set email alerts
|

The FGLOCTweet Corpus: An English tweet-based corpus for fine-grained location-detection tasks

Abstract: Location detection in social-media microtexts is an important natural language processing task for emergency-based contexts where locative references are identified in text data. Spatial information obtained from texts is essential to understand where an incident happened, where people are in need of help and/or which areas have been affected. This information contributes to raising emergency situation awareness, which is then passed on to emergency responders and competent authorities to act as quickly as pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, recent research has shown that many location descriptions are not in the form of simple place names (e.g., city names or street names) but consist of multiple entities (Y. Hu and Wang 2021;Fernández-Martínez 2022;Chen et al 2022). Examples of these more complex location descriptions include door number addresses, road intersections, highway exits, and road segments.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has shown that many location descriptions are not in the form of simple place names (e.g., city names or street names) but consist of multiple entities (Y. Hu and Wang 2021;Fernández-Martínez 2022;Chen et al 2022). Examples of these more complex location descriptions include door number addresses, road intersections, highway exits, and road segments.…”
Section: Introductionmentioning
confidence: 99%